Effects of pretreatment with cardiostimulants and beta-blockers on isoprenaline-induced takotsubo-like cardiac dysfunction in rats. (15th April 2019) - Ali, Anwar; Redfors, Björn; Lundgren, Joel; Alkhoury, Jessica; Oras, Jonatan; Gan, Li-Ming; Omerovic, Elmir
Abstract: Background: Takotsubo syndrome (TS) is an acute cardiac syndrome characterized by regional myocardial akinesia that is not caused by coronary artery occlusion. Exogenous as well as endogenous excess catecholamines can induce TS. The aim of this study was to explore the effects of pharmacological cardio-simulative and cardio-depressing drugs on the development of isoprenaline-induced takotsubo-like cardiac dysfunction, a rat model of TS. Methods: We randomized 295 rats into twelve groups. The animals were randomized to pre-treatment with either a low or high dose of metoprolol, propranolol, ICI 118551 (beta2 -receptor antagonists), milrinone (phosphodiesterase inhibitor), levosimendan or saline (control) before induction of TS with isoprenaline. In one additional group, high dose of milrinone was administered alone. We measured invasively blood pressure and heart rate over a period of 90 min. Cardiac function and morphology were evaluated with high-resolution echocardiography. Results: Milrinone alone induced apical ballooning similar to isoprenaline. Pretreatment with propranolol and metoprolol but not with ICI 118551 attenuated takotsubo-like akinesia in a dose-dependent manner. Pretreatment with metoprolol decreased mortality. Pretreatment with levosimendan resulted in higher incidence of apical ballooning while pretreatment with milrinone did not change the degree of akinesia. Conclusion: The phosphodiesterase inhibitor milrinone induces takotsubo-like dysfunction in the absence of exogenous catecholamines. This finding challenges the concept that high levels of circulating catecholamines or excessive stimulation of adrenergic receptors are necessary for the development of takotsubo syndrome. Our study provides experimental evidence for the concept of avoidance of inotropes and that selective beta1 -blockade may be beneficial in the treatment of TS-patients. Highlights: Cardiostimulants exacerbate whereas cardiodepressants attenuate isoprenaline-induced takotsubo-like cardiac dysfunction in rats. Milrinone administration can induce takotsubo-like dysfunction in rats without concomitant administration of catecholamine. High levels of circulating catecholamine may not be necessary for the development of takotsubo.